Effect of Hydrophilic Polymer and Binder on Drug Release of Metformin HCL in Sustained-Release Matrix Tablet - Kakad, Sudarshan B. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of this study was to develop a sustained release formulation containing Metformin HCl. Methods: The sustained-release Metformin HCl tablet was prepared by wet granulation technique, using different grades of hydroxyl propyl methylcellulose (HPMC) in different concentration and by varying binder concentrations. Formulation optimization was done by three ways to select optimum formula for preparing sustained-release matrix tablet. The trail batches were prepared by varying the concentration of the binder and hydrophilic polymers, and they were all analyzed for pre-and post-compression parameters. To determine the concentration of HPMC K4M in the first step, three trial batches are produced. The following three batches are, then, analyzed to measure the concentrations of HPMC K15M and K100M in the second and third steps, respectively. The HPMC amount was optimized at 240 mg. Results: Each optimized HPMC batch’s drug release was assessed in an in vitro drug release trial using phosphate buffer solution at pH 6.8 and compared to the drug release of the commercial formulation. Drug identification was performed by melting point determination, Fourier transform infrared, UV, and solubility determination. After pre-compression and post-compression evaluation, we get the appropriate result in B3, B6, and B9 batches. In vitro drug release of these three batches was studied and compare with the marketed formulation. Formulation when compared to the reference sustained-release Metformin HCl tablet, batch B9’s drug release, was very similar. Batch B9 is therefore an optimized formulation. Conclusion: The hydrophilic polymer HPMC K100M is useful for making tablets of metformin HCl with sustained-release. With an increase in hydrophilic polymer content, the drug release was prolonged, and the PVP K30 binder gave the tablet the right amount of hardness.